Allergy to hypoallergenic nail polish: does this exist? - Rosana Lazzarini; Mariana de Figueiredo Silva Hafner; Andressa Sato de Aquino Lopes; Camilla Bilac Oliari (Sociedade Brasileira de Dermatologia, 2017)
Abstract The main allergen responsible for contact dermatitis to nail polish is tosylamide-formaldehyde resin. The so-called hypoallergenic nail polishes are suposedly free of agents that commonly trigger reactions. The commercially available products and their compositions were studied. It was observed that most brands present at least one component capable of triggering the disease; therefore, allergic reaction may occur even when hypoallergenic polishes are used. There should be a proper investigation of the specific allergen through a patch test, because more than one component can cause an allergy, and we need to check the exact composition of each product.